Improving the efficiency and selectivity of Cd2+ removal using a modified resin in the continuous electropermutation process. Issue 11 (23rd July 2020) - Mehellou, Ahmed; Delimi, Rachid; Benredjem, Zahia; Saaidia, Samia; Allat, Lamia; Innocent, Christophe
ABSTRACT: This study was undertaken to enhance the selectivity and the removal efficiency of Cd 2+ from a mixture solution containing Cd 2+ and Na + using continuous electropermutation (EP) with alginate-modified resin (MR). The surface of the MR was characterized via scanning electron microscopy and Fourier transform infrared. The use of the MR in EP process has improved the efficiency and the selectivity for Cd 2+ removal from Cd 2+ (88, 46%), Na + (81, 41%) to Cd 2+ (96, 98%), Na + (51, 47%). The effect of current density and concentration of the electro-regeneration electrolyte on the Cd 2+ removal efficiency was investigated. Abbreviations: AEM, anion-exchange membrane; AG, alginate; CEM, cation-exchange membrane; DS, desorption solution; DVB, divinylbenzene; EDI, electrodeionization; ED, electrodialysis; EP, electropermutation; ERE, electroregeneration electrolyte; FTIR, Fourier transforms infrared; IER, ion-exchange resins; LG, glucuronic acid; MR, modified resin; SEM, scanning electron microscopic; UMR, unmodified resin; DM, D-mannuronic.